Cooling Energy and Passive Energy Saving Strategies for Master Bedroom of a Tropical Bungalow House - Sabouri, Saber; Mohd Zain, Mohamad Fauzi (Journal of Surveying, Construction and Property, 2011)
Bungalow as a low density house is one of the three major house types in Malaysia. In tropical countries, cooling of spaces has a main portion of energy consumption of buildings. In Malaysian houses, bedrooms are cooled mostly and it occurs in nighttime. In this study, a bungalow house was simulated by DesignBuilder software and calibrated with its annual electrical bills. Then, effects of five passive strategies were explored separately. Results showed that applying appropriate window and proper insulation could save 72.6% and 36.4% cooling energy of master bedroom, respectively. Maximum saving of cooling energy due to best orientation was 12.3%. Higher ratio of window to wall area for north wall was more suitable than west wall. But difference of their cooling energy was not so intensive. Existence of balcony with 1.6m depth attached to external walls of master bedroom will save 31% chiller electricity compared to without balcony condition. Integration of these strategies in a bungalow house showed approximately no need for cooling energy of master bedroom with 28°C cooling set point. Also, it was 97.5% and 87% saving of cooling energy with 27°C and 26°C cooling set points of master bedroom, respectively. Keywords: Simulation, Bungalow house, Cooling Energy, Passive Energy Saving, Chiller Electricity